Arsenic (III) removal by mechanochemically sulfidated microscale zero valent iron under anoxic and oxic conditions. (15th June 2021) - Zhao, Jiawei; Su, An; Tian, Ping; Tang, Xianjin; Collins, Richard N; He, Feng
Highlights: As(III) can be effectively removed by ball milled, sulfidated ZVI (S-mZVI bm ). As(III) was removed primarily through As4 S4 formation under anoxic conditions. As(III) was removed through adsorption onto corrosion product under oxic conditions. S-mZVI bm /sand column rapidly reduces As(III) in a groundwater from 300 to 10 µg/L. S-mZVI bm in sand column treats >750 BV groundwater with a capacity of 12.2 mg/g. Abstract: The interaction of As(III) with micron-sized, mechanochemically sulfidated zero-valent iron (S-mZVI bm ) has been studied under both anoxic and oxic conditions. The As(III) removal capacity varied with the increase of S/Fe molar ratio under anoxic conditions, while it continuously decreased under oxic conditions. A series of sequential extractions, X-ray photoelectron spectroscopy (XPS) and X-ray absorption near edge structure (XANES) spectroscopy analyses were used to investigate As(III) removal mechanisms. In the absence of oxygen, As(III) was removed from solution primarily through the formation of As4 S4 with less than half of the removal resulting from the adsorption of As(III)/As(V) and FeAsS precipitation. Under oxic conditions, adsorption onto iron (oxyhydr)oxides was the dominant mechanism of As(III) removal. Increasing sulfidation decreased particle Fe(0) content, which resulted in less production of iron (oxyhydr)oxides and therefore lower As(III) removal capacities. Column experiments showed that less than 2 wt% of S-mZVI bm in sand was able to rapidly reduce the As(III) concentration in a real groundwater from 300 to 10 µg/L, the Chinese drinking water standard, for up to 750 BV with an EBCT of 2.54 min. This study demonstrates that S-mZVI bm is an efficient and cost-effective material in treating As-contaminated water to ensure water safety. Graphic abstract: Image, graphical abstract